Harnessing Natural Aryl Aldehydes to Synthesize Bromochalcones as Anticancer Candidates Targeting Proliferative Pathways - Setyawati, Amri; Prasetyo, Niko; Kartini, Indriana; Astuti, Endang; Wahyuningsih, Tutik Dwi (Trends in Sciences, 2026)
Current cancer therapies are limited by sustainability, drug resistance, and off-target effects. Bromochalcones are suitable candidates for targeted therapies, owing to their designable structure that can engage proliferative pathways. This study aimed to synthesize bromochalcones from natural aryl aldehydes and to evaluate their structural features and in vitro and in silico anticancer properties. Six bromochalcones were synthesized and identified by FTIR, GC-MS, and NMR. The in vitro MTT assay showed that all brominated chalcones were more cytotoxic toward HeLa cells than toward MCF-7, T47D, and Vero cells. Compound (E)-1-(4-bromophenyl)-3-(4-hydroxy-3-methoxyphenyl) prop-2-en-1-one (referred to 2D), derived from vanillin, achieved the best results (IC50 = 5 µg/mL; SI = 90.71), outperforming doxorubicin (IC50 = 15 µg/mL). Molecular docking studies on several proliferation proteins indicate that PCNA had the highest correlation between binding affinity and the in vitro IC50 trend. 2D-PCNA complex exhibited the strongest binding affinity by forming hydrogen bonds with Glu25, Met40, and His44. A 100 ns molecular dynamics simulation also shows a stable interaction with a strong binding affinity. Reactivity analysis from DFT calculations indicates that bromochalcones 2A and 2D were the 2 most potent compounds in driving interactions, including hydrogen bonding. Furthermore, ADMET predictions assessment reveals the safety and potential of these compounds as drug candidates. In conclusion, vanillin-derived bromochalcone, 2D, emerges as the lead compound, demonstrating the best in vitro anticancer activity, a favorable in silico profile, and the highest potential for development into various formulations. HIGHLIGHTS Six bromochalcones derived from natural aryl aldehydes were screened for their effects on breast and cancer cells in vitro and in silico. Vanillin-derived bromochalcone 2D inhibited HeLa cell viability (IC₅₀ = 5 µg/mL, 48 h), showing 3-fold higher potency than the reference drug doxorubicin under the same assay conditions. Integrated docking, molecular dynamics, DFT descriptors, and ADMET predictions suggest that bromochalcone 2D has stable binding to PCNA and a favorable drug-likeness profile, supporting its prioritization for further mechanistic validation. GRAPHICAL ABSTRACT